Wind power dynamic behaviour - Real case study on Linderödsåsen wind farm - Wang-Hansen, Mats (My University, 2008)
Rapid wind power development has led to a shift from small generators to large generators and from single distributed units to large centralised clusters of generators commonly known as wind farms. This substantial structural difference has invoked power system stability issues related to wind power. Large, centralised power plants of conventional types have always been forced by regulation to stay online and support the grid during voltage dips, but for wind farms no such regulation have historically existed. In 2005, the Swedish transmission system operator (TSO) acknowledged the forthcoming need for regulation and issued a new grid code including connection requirements for wind power generation. The new grid code describes different fault scenarios in the high voltage network which generators are supposed to ride through without disconnection. The new grid code applies to all facilities commissioned or rebuilt after 2006. In this study, the grid code scenarios are simulated, and the resulting wind power dynamic behaviour is examined to establish the implications of the grid code for wind farm grid connections in Sweden. HS Kraft’s planned wind farm at Linderödsåsen in southern Sweden is considered to be of relevant proportions (90 MW) and is chosen as a real case study. A PSS/E model of the wind farm is subjected to the fault scenarios described in the grid code, and the resulting voltages at the different busses in the test system are monitored along with wind turbine generator (WTG) active and reactive power response. The two dominating WTG technologies, doubly fed induction generator (DFIG) and permanent magnet synchronous generator (PMSG), are compared and evaluated both from a wind farm developer perspective, and from a grid owner/TSO perspective. Additionally, low voltage ride through (LVRT) settings from three large WTG manufacturers are compared with the simulated residual voltages at the WTG transformer high side to determine their degree of compliance with the grid code. All simulation results show WTG high side residual voltages that are within the LVRT capabilities of the wind turbines at offer for the planned wind farm investigated. A wind farm consisting of PMSG turbines run in reactive power injection mode experience higher residual voltages at the transformer high side than a farm consisting of DFIG turbines. But the DFIG turbine farm experience higher residual voltage than normal mode run PMSG-turbine farm. Both DFIG and PMSG technologies deliver more reactive current when operating at low speeds due to the limited current carrying capabilities of the DC-link converters. The collector network layout is of minor importance to the residual voltage level at the wind turbine transformer high side, and the DFIG LVRTactions cause considerable stress to its mechanical drive train.
Keywords: Elkraftteknik; Electric power engineering